Analysis Of Disability And Stigma On Self-Concept On Leprosy Patients - Srinalesti Mahanani; Desi Natalia Trijayanti Idris (Universitas STRADA Indonesia, 2020)
The research design used was correlation analysis with cross sectional data collection. The population was all leprosy patients in the outpatient installation of the Daha Husada General Hospital with a total sample of 50 respondents who were selected using the purposive sampling technique. Measurement of disability is developed from the standard provisions of the Ministry of Health of the Republic of Indonesia. Stigma measurement uses the Internalized Stigma of Mental Illnes Scale (ISMI) which was developed by The International Federation of Anti-Leprosy Associations (ILEP) in 2011. Meanwhile, the Self-Concept instrument is developed from indicators according to theory. The analysis used was logistic regression starting with the examination of the variables and the results were p value = 0.40 for disability and p value = 0.49 for stigma. It can be interpreted that disability gives potential 5,652 times and stigma gives potential 6,205 times for self-concept